Upaya Madrasah Membangun Hard dan Soft Skill Siswa dalam Kesiapsiagaan terhadap Bencana di MI I Bantul - Nindya Rachman Pranajati (Jurnal Pendidikan Madrasah, 2018)
Its natural state and its geographic that are vulnerable to natural disasters and preparedness society that still minimal, so that required awareness about preparedness to reduce the risk of disasters, one of which is through education.This study attempts to described efforts madrasah in build hard and soft skills students for preparedness for disasters.The research is field research, with the approach descriptive qualitative.The data collection was done using observation, in-depth interviews, and documentation.The method of analysis the data used in this research was reduction data, presentation of, and conclude.Examination the validity of this data use technique triangulation, member check, and increase reference. This research result indicates efforts madrasah in developing hard and soft skills students to preparedness for disasters through the islamic strategic policy, intrakurikuler learning activities, extracurricular, pembiasaan, and through cooperation with related parties to kebencanaan. In the intrakurikuler, soft skills students in basic knowledge in dealing with disasters, social care, an attitude toward the developed through talks with the interactive learning, discussion, training facilities use library and nurse as the source. For teaching, would be integrated into the subject is. In extracurricular activities, the efforts to build up the hard skills students be integrated into the direct practices in the simulation disaster held regularly and extracurricular activities the boy scouts. Besides that there training by the nurse, pmi, and community health centers. The policy of the head master of madrassa Islamic religious scool by the daily activities can make the cultures of preparadness for students.